2022
DOI: 10.3389/fimmu.2022.871713
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Intestinal Mucosal Barrier in Autoimmune Disease: A Potential Target

Abstract: Autoimmune diseases are a series of diseases involving multiple tissues and organs, characterized by the over production of abnormal multiple antibodies. Although most studies support that the impaired immune balance participates in the development of autoimmune diseases, the specific pathogenesis of it is not fully understood. Intestinal immunity, especially the intestinal mucosal barrier has become a research hotspot, which is considered to be an upstream mechanism leading to the impaired immune balance. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 99 publications
0
50
0
Order By: Relevance
“…The intestinal physical barrier is a complete intestinal epithelial structure composed of intestinal epithelial cells and tight junctions [ 45 ]. The tight junction is a complex protein system formed by the interaction of a series of transmembrane proteins and peripheral proteins, which can be regulated in many ways [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal physical barrier is a complete intestinal epithelial structure composed of intestinal epithelial cells and tight junctions [ 45 ]. The tight junction is a complex protein system formed by the interaction of a series of transmembrane proteins and peripheral proteins, which can be regulated in many ways [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intercommunication between the host and gut microbiota at the intestinal barrier regulate mucosal and systemic immune responses and, in pathological states, may result in aGVHD [6,45,46]. It suggested that the gut microbiota is closely related to the expression of tight junction proteins [47]. The present study showed that the mRNA expression of TJs ZO-1 and Occludin was negatively correlative to the relative abundance of harmful bacteria whereas had a positive correlation to beneficial bacteria, indicated that the gut microbiota was important to maintain the integrity of the intestinal barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, our results showed that exogenous cysteine supplementation at 0.6% and 1.2% greatly improved intestinal villus length and muscular thickness, thus effectively alleviating the weakening of the intestinal physical barrier associated with low-fishmeal diets. Alterations in the intestinal physical barrier typically accompany changes in the abundance of intestinal flora ( 52 , 53 ) and expression of intestinal immune-related genes ( 54 ). Therefore, we propose that the protective effect of cysteine on the intestinal physical barrier of golden pompano may be correlated with increased abundance of intestinal flora and high expression of intestinal antioxidant stress- and immune-related genes.…”
Section: Discussionmentioning
confidence: 99%